OPTIMALISASI PENGGUNAAN MEDIA GAMBAR DALAM PENINGKATAN PENCAPAIAN KRITERIA KETUNTASAN MINIMAL (KKM) BAHASA INDONESIA SISWA KELAS I SDN 20 CAKRANEGARA - MUSIYATI, HJ. (Universitas Mahasaraswati Mataram, 2019)
This research is a Classroom Action Research which consists of two cycles where each cycle consists of four stages, namely the stages of planning, implementation, observation, and reflection. Please note that each cycle consists of 3 meetings. The background of this research is the low achievement of KKM in each of the Basic Competencies (K.D), especially in Indonesian language subjects. This study aims to improve the learning outcomes of Indonesian language class I students by optimizing the use of image media. The research subjects were first grade students of SD Negeri 20 Cakranegara first semester 2017/2018 Academic Year with a total of 47 students. Data is obtained through observation during the learning process takes place, giving group assignments and the results of discussions and tests of student learning outcomes given at the end of each cycle. Data analysis uses descriptive qualitative and quantitative in the form of averages and the percentage of improvement in learning outcomes. The results of the analysis show an increase in the achievement of student KKM scores each cycle. From the results of student learning tests in the first cycle, data obtained that the achievement of student learning completeness reached 66.67%, and in the second cycle increased to 86.96%. The results of the study showed that optimizing the use of image media can improve the achievement of KKM Indonesian language subjects in class I Cakranegara State Elementary School 20